MODAL SOSIAL DALAM STRATEGI KOMUNIKASI POLITIK - Siswanto Siswanto (Universitas Lambung Mangkurat, 2019)
Since the 1998 reformation until the 2014 election, politics in our country was characterized by massive transactional practices. It had been regarding to money politics practiced very obvious in every political event in choosing either in the executives or the representative’s level. However, the more interesting thing, with the rampant practice of transactional culture in the legislative election, is that there were the only few of people who dared to against such issue. This research employs a qualitative research paradigm with using a case study approach in which researcher had found that a political modality of Aziz Kahar Muzakkar is examined in a very strong social capital. Communication strategies which were person campaign strategies, adhesive strategies, structural strategies, cultural strategies as well as the strategy of collaboration between religion and development massages and propaganda techniques. This research also reveals a dominant model of political communication messages was propaganda. The conclusion is that the number of legislative members having a limited budget could be elected in the current transactional politics era. The key for this is to strengthen and maintain social capital in the community, and the communication strategy is in accordance with the political modality owned during the election campaign.